Respiratory failure in confirmed synthetic cannabinoid overdose. (3rd April 2022) - Manini, Alex F.; Krotulski, Alex J.; Schimmel, Jonathan; Allen, Lisa; Hurd, Yasmin L.; Richardson, Lynne D.; Vidal, Kavey; Logan, Barry K.
Abstract: Context: Synthetic cannabinoids (SCs) are a structurally heterogenous synthetic class of drugs of abuse. The objective was to describe the incidence of acute respiratory failure in Emergency Department (ED) patients with confirmed SC exposure, and to investigate the association between SC overdose with respiratory failure compared to non-SC overdose. Methods: This was an observational cohort of ED patients ≥18 years with suspected cannabinoid overdose between 2015 and 2020 at two tertiary-care hospitals. Patient serum was analyzed via liquid chromatography/quadrupole time-of-flight mass spectrometry using a library with >800 drugs including novel psychoactive substances. The primary outcome was acute respiratory failure. Discussion: Of 83 patients with suspected cannabinoid overdose, there were 29 confirmed SC overdoses: 5 F-MDMB-PICA ( n = 18) and its metabolite 5OH-MDMB-PICA ( n = 16), ADB-FUBINACA ( n = 4), AB-CHIMINACA ( n = 4), AB-FUBINACA ( n = 1), AB-PINACA ( n = 1), MDMB-4en-PINACA ( n = 1), and 4 F-MDMB-BINACA ( n = 1). Overall, incidence of acute respiratory failure was 31.3% (95%CI 21.6–42.4). Compared to non-SC overdose, confirmed SC overdose was significantly associated with respiratory failure (25.0% SC vs. 4.2% non-SC, p = 0.05). Conclusion: This study demonstrates that SCs are associated with respiratory failure. Since respiratory depression is a potentially lethal adverse effect of SC overdose, future research is warranted.